Methods of prevention and treatment of alveolar osteitis - Ya. A. Rakhmanov; Z. S. Khabadze; A. Machin; M. M. Borlakova; N. N. Fedortova; M Yu. Dashtieva (LLC "Endo Press", 2022)
Alveolar osteitis is an infectious complication after tooth extraction. They appear in two forms: serous, characterized by pain syndrome and decayed clot, purulent, which is identified by provoked pain and filling of alveoli, and chronic hypertrophic, in which body temperature decreases and general well-being improves.Aim. To explore different methods of preventing and treating alveolar osteitis.Alveolar osteitis usually occurs more frequently in young adults between the ages of 30 and 50 and is slightly more common in women than in men. Treatment methods for dry socket are quite limited, but there are a large number of drugs for treatment: eugenol-based drugs, chlorhexidine, antibiotics, analgesics and local anesthetics, enzymes, hemostatic agents, hormonal agents soaked in collagen sponges, pastes, gels, turundas, preparations based on biopolymers such as chitosan, and platelet-rich plasma.